2020
DOI: 10.1364/ao.392126
|View full text |Cite
|
Sign up to set email alerts
|

Validation of uniformity-optimized irradiance distribution on a well-plate platform from a light-emitting-diode array

Abstract: The computational optimization of irradiance distribution uniformity has been conducted in several studies to obtain the evenness of photoresponses on an irradiated surface using light-emitting-diode (LED) arrays. However, there has been little discussion on the precision of predictive simulations. This study aims to validate the simulated irradiance predicted by a mathematical model on the working area of a six-well plate and investigate the spatial consistency of the photobleaching of methylene blue and IR-8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…[55][56][57][58] Figure 3C shows a temperature measurement method using a contact thermometer during surface-lighting irradiation on a human wrist. Figure 3D; Figure S14, Supporting Information, exhibits temperature changes of the 30 × 30 SμLEDs at five different input currents (20,40,80, 100, and 120 mA). Despite 120 mA current injection, the device temperature remained below 39 °C for 10 min.…”
Section: The Characteristics Of Sμled Patch For Wearable Phototherape...mentioning
confidence: 99%
See 1 more Smart Citation
“…[55][56][57][58] Figure 3C shows a temperature measurement method using a contact thermometer during surface-lighting irradiation on a human wrist. Figure 3D; Figure S14, Supporting Information, exhibits temperature changes of the 30 × 30 SμLEDs at five different input currents (20,40,80, 100, and 120 mA). Despite 120 mA current injection, the device temperature remained below 39 °C for 10 min.…”
Section: The Characteristics Of Sμled Patch For Wearable Phototherape...mentioning
confidence: 99%
“…[1] Various treatments including physical, chemical, and optical with ≈2 cm radiation distance leads to non-uniform irradiation, requiring more vertical distance to evenly cover the 3D faces with the light. [20] While light uniformity can be improved by increasing vertical distance, the optical power density at the skin surface is significantly reduced by the long radiation distance and severe diffuse reflection. [21,22] Some researchers reported that only 10% of incident light could penetrate into a skin model when irradiated with a 630 nm light source at 2 cm distance.…”
Section: Introductionmentioning
confidence: 99%